Clonal micropropagation of bog cranberry (Vaccinium oxycoccos L.) in the Udmurt Republic - E. N. Cheremnykh; T. G. Lekontseva; A. V. Khudyakova; A. V. Fedorov (Аграрная наука Евро-Северо-Востока, 2021)
The paper presents the results of 2018-2019 research on improving the technology of growing planting material of bog cranberry (Vaccinium oxycoccos L.) of Krasa Severa, Severyanka, Virussaare varieties on the basis of in vitro. Studied was the effect of the concentrations of growth regulators in the composition of the nutrient medium according to Anderson's recipe on the reproduction and subsequent rooting of micro cuttings, as well as the duration of cultivation and adaptation of micro plants depending on partial pruning of shoots. It has been established that at the stage of introduction into in vitro culture, sterilization of explants with 33% hydrogen peroxide in an exposure of 5-8 minutes with washing in 5 portions of sterile distillate gives 60-80 % of viable shoots. The optimum phase of plant development for the successful introduction of in vitro culture is the swelling of buds. Cultivation of micro cuttings was carried out in a light room at a temperature of 25±2 °С, a photoperiod of 16 hours. The duration of each subculturing was 30-60 days. For the stage of actual micropropagation on Anderson's nutrient medium, an increase in the dose of cytokinin 6-benzylaminopurine (6-BAP) from 0.2 to 0.5 mg/l and an increase in the duration of cultivation from 30 to 60 days contributed to a significant increase in the multiplication factor on average for the tested cranberry varieties.According to the efficiency of micropropagation, the varieties Virussaare and Krasa Severa were distinguished – 9.3-12.0 pcs/stalk, respectively. At the rooting stage, the use of a root-forming reagent of indolyl-3-acetic acid (IUK) in doses of 0.2, 0.5 and 1.0 mg/l in the composition of Anderson's nutrient medium did not affect the quality of root formation and the length of shoots of Virussaare micro-plants. No significant varietal differences in the root-forming ability of microcuttings were found. The tendency of better rooting of micro cuttings was observed in the Virussaare variety (90.3 %) compared to the Severyanka (85.7 %) and Krasa Severa (79.3 %) varieties. Micro plants of the Krasa Severa cultivar were characterized by the longest shoots, the total number of roots was less, but their length was longer in comparison with other cultivars. For the adaptation stage, a substrate from a mixture of lowland peat and sphagnum moss was used (1:1). The efficiency of adaptation of micro plants of cranberry varieties when cutting the tip of the shoots was 100 %. Pruning of micro plants shoots contributed to the formation of more side shoots and better development of the aboveground part of the plants.